As We Were Saying - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"As We Were Saying" by Charles Dudley Warner is a collection of essays written during the late 19th century. The book explores various cultural observations and trends of the time, addressing social issues, fashion, and the changing dynamics of gender roles. Warner examines themes such as the superficiality of societal conventions, the responsibility of writers, and the nature of civilization in an ever-evolving world. The opening of the book sets the stage for its reflective tone, starting with the piece "Rose and Chrysanthemum." In this segment, Warner contrasts the traditional beauty of the rose with the garishness of the chrysanthemum, symbolizing changing societal tastes and the ephemeral nature of fashion. He ponders whether modern life, characterized by ostentation and show, leads to a loss of intrinsic values and genuine sentiment. Warner uses this floral metaphor to delve into deeper questions about individuality, meaning, and the moral implications of changing trends, establishing a framework for the thoughtful critiques present throughout the collection. (This is an automatically generated summary.)
Rose and chrysanthemum -- The red bonnet -- The loss in civilization -- Social screaming -- Does refinement kill individuality? -- The directoire gown -- The mystery of the sex -- The clothes of fiction -- The broad A -- Chewing gum -- Women in Congress -- Shall women propose? -- Frocks and the stage -- Altruism -- Social clearing-house -- Dinner-table talk -- Naturalization -- Art of governing -- Love of display -- Value of the commonplace -- The burden of Christmas -- The responsibility of writers -- The cap and gown -- A tendency of the age -- A locoed novelist.
Release date is 2004-12-05
Produced by David Widger
Keywords: Essays